Changes in bird assemblages in a wetland ecosystem after 14 years of intensified cattle farming - Sica, Yanina Vanesa; Gavier Pizarro, Gregorio Ignacio; Pidgeon, Anna Michle; Travaini, Alejandro; Bustamante, Javier; Radeloff, Volker C.; Quintana, Rubén D. (2018)
Human activities have modified wetlands all over the word. Water control structures that are frequently implemented in these ecosystems to keep lands free of flooding can decrease or degrade habitat for biodiversity. The Paraná River Delta, one of the largest wetlands in Argentina, has recently experienced rapid cattle grazing intensification facilitated by water control structures, resulting in extensive conversion of wetlands to pastures. It is unclear if this loss of wetlands has had a negative impact on the highly diverse bird community. Here, we evaluated the changes in bird assemblages in the Lower Delta of Paraná River after 14 years of cattle grazing intensification. We compared point count data from 1997 to 1999 with data collected in 2012 and 2013 using the same survey methods. We assessed the temporal changes in bird richness and composition using paired permutation tests and multivariate analysis. We related the bird composition to landscape changes to analyse if avian changes were associated with landscape dynamics. We found that after 14 years, the bird community differed greatly. In general, species richness decreased, especially in wet years. We found fewer wetland species in recent surveys; in particular we did not register saffron‐cowled blackbird (Xanthopsar flavus), a species listed as globally vulnerable. Changes in bird composition were associated with an increase in bare soil due to land‐use changes. Even though inter‐annual differences in precipitation and river stage have great effects on the species present in the surveys, the absence of many wetland species in recent wet years, that is when habitat is suitable for them, is most likely due to changes in land cover. Globally, agricultural land use makes inroads into many wetlands, eroding their quality and extent. Maintenance of wetland species requires that conservation efforts focus on these vulnerable ecosystems before full‐scale land conversion occurs.